Putusan MK nomor 97/PUU-XIV/2016 dan Pengaruhnya Terhadap Perubahan Identitas Perempuan Penghayat - Rindang Farihah (UIN JAKARTA, 2020)
The enactment of Law No.1/PNPS/1965 concerning Prevention of Abuse and/or Religion Blasphemy impacts on the exclusion of sects of belief in Indonesia from the recognised religions in Indonesia. The existence of the cults has long become polemic and debates in Indonesia. As a result, native-faith followers have experienced discrimination, stigmatisation and exclusion in society. The issuance of the Constitutional Court Decision number 97/PUU-XIV/2016 at the end of the year at the end of 2017 became a momentum for adherents of the faith to get recognition of their identity.Believers have been equalized with official religions in Indonesia. This article discusses the reality related to the effect of the implementation of the Constitutional Court ruling on the religious identity of believers. Based on the data, it was found that some believers still chose not to change their religious identity on the KTP. They are still comfortable with their identity, and changing religious identities is not a priority.